Differences in approach run kinematics: successful vs. unsuccessful jumps in the pole vault - Cassirame, J.; Sanchez, H.; Exell, T. A.; Panoutsakopoulos, V.; Theodorou, A. S.; Homo, S.; Frère, J. (International Journal of Performance Analysis in Sport, 2019)
This study investigated biomechanical differences between successful and unsuccessful jumps during a pole vault competition. Two hundred and seven pairs of successful and unsuccessful jumps at the same height were analysed. Participants included male and female athletes of three different age groups with bar height clearances ranging from 2.81 to 5.91 m. Run-up parameters were collected using an Optojump Next system and a Stalker Pro II radar gun. A 2D kinematical analysis was conducted to obtain selected parameters of the take-off. Only trivial and small differences were found between successful and unsuccessful jumps. The speed at last touchdown showed a significant small difference between successful and unsuccessful jumps, as the greater speed at take-off (+0.15 m/s) was observed at successful jumps compared to unsuccessful jumps. Furthermore, female athletes showed a significant small difference in horizontal hand-foot distance between successful jumps and unsuccessful jumps (+0.05 m and +0.06 m at pole plant and take-off, respectively). The results suggest that pole vaulters should produce a fast run-up and avoid a decrease in speed before take-off. Small adjustments in the take-off posture might increase the transfer of energy from the athlete to the pole and thus an improvement concerning the height of bar clearance.